2016
DOI: 10.1038/srep32804
|View full text |Cite
|
Sign up to set email alerts
|

CD147/EMMPRIN overexpression and prognosis in cancer: A systematic review and meta-analysis

Abstract: CD147/EMMPRIN (extracellular matrix metalloproteinase inducer) plays an important role in tumor progression and a number of studies have suggested that it is an indicator of tumor prognosis. This current meta-analysis systematically reevaluated the predictive potential of CD147/EMMPRIN in various cancers. We searched PubMed and Embase databases to screen the literature. Fixed-effect and random-effect meta-analytical techniques were used to correlate CD147 expression with outcome measures. A total of 53 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 68 publications
3
88
1
6
Order By: Relevance
“…HG‐EMMPRIN on the plasma membrane is considered to be the biologically functional form of EMMPRIN . Previous studies have shown that EMMPRIN on tumor cells stimulated stromal fibroblasts to produce MMPs, leading to ECM degradation and promoting tumor growth and metastasis . An HG‐EMMPRIN counter‐receptor may exist on the fibroblast cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…HG‐EMMPRIN on the plasma membrane is considered to be the biologically functional form of EMMPRIN . Previous studies have shown that EMMPRIN on tumor cells stimulated stromal fibroblasts to produce MMPs, leading to ECM degradation and promoting tumor growth and metastasis . An HG‐EMMPRIN counter‐receptor may exist on the fibroblast cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…CD147 is widely expressed on the cell surface of different cancer types [8]. CD147 has been demonstrated to facilitate the synthesis and secretion of matrix metalloproteinases (MMPs)[9].…”
Section: Introductionmentioning
confidence: 99%
“…24 As previously reported, CD147 is a tumor-associated antigen highly enriched on the surface of various malignant tumor cells, 25 and it is involved in the neoplastic cell behavior of tumors via CD147-mediated matrix metalloproteinase (MMP) production and interaction with various ligands. 26,27 As such, CD147 has also been suggested as an early diagnostic biomarker and a significantly unfavorable prognostic factor for various malignant tumors, 28 including NSCLC. 29 More importantly, CD147 has been demonstrated to promote glucose metabolism reprogramming in hepatocellular carcinoma.…”
mentioning
confidence: 99%